Bronchial asthma: a risk factor for hypertension? (2000)
Several attempts have been made to improve primary prevention of essential hypertension and many of these have been directed at avoiding the well known risk factors. Both asthma and hypertension are spastic disorders of smooth muscle, also asthmatics and hypertensives have been found to be salt sensitive. There is a suspicion that the similarities between these two diseases may predispose the individuals with one disease to the other, as pulmonary hypertension has been described during exercise- induced bronchoconstriction. We therefore, studied the blood pressure pattern during and after acute severe asthma (ASA) along with the frequency of hypertension in stable asthmatic patients. Two groups of patients were studied. Group 1 consisted of 12 patients with ASA (2 males, 10 females) with a mean age of 30 ± 9,9.years. The mean blood pressure during attack of ASA (147±16.9/ 100±8.2 mmHg) was higher than the mean BP (132±8.3/82±7 mmHg) 2 weeks after discharge from hospital without treatment in all patients (P < 0.05). Group 2 included 134 asthmatic subjects in stable state (54 males, 80 females) with a mean age of 45 ± 15 years and a range of 15-90 years. The overall frequency of hypertension was 37% with a proportion of 39% in males and 35% in females. Hypertension was defined as systolic blood pressure of £ 140mmHg and or diastolic blood pressure of £ 90mmHg. There was no difference between the frequency of attack of ASA in hypertensives (5.7 ±5.6 per year) and nonhypertensives (5.5 ± 3.8 per year), P < 0.05. We concluded that transient elevation of blood pressure may occur during ASA. The frequency of hypertension among asthmatics is quite high and concurrent family history of hypertension and frequency of attack of ASA did not seem to determine the status of blood pressure. Patients with asthma should have regular blood pressure check during follow-up visits.